Endangering Child Rearing and The Quality of Family Communication: Socio-Psychological Impact of Women Migrant Workers Overseas - Tiara Kusuma Wardhani; Safira Amanda; Khanna Maulidya Dika Bintari; Putri Regina Januarizka; Naufal Azfa Setiyanto; Tiara Putri Valentina; Maritza Alifah Zamir; Muhammad Bayu Sulthan; Ganesh Zernikeridzki Gunawan; Agus Joko Pitoyo (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The migration of female Indonesian migrant workers (PMI) is a growing phenomenon in rural areas in response to limited employment opportunities and economic pressures on households, including in Sendang Subdistrict, Tulungagung Regency. This study aims to analyze the impact of female PMI departure on the socio-psychological conditions of households, particularly changes in domestic roles, child-rearing patterns, and the quality of family communication. The study uses a quantitative descriptive approach through structured interviews, observation, and documentation. The results of the study show a shift in gender roles within households, marked by the takeover of domestic and childcare tasks by husbands or other family members. In addition, the intensity and quality of long-distance communication has a significant effect on emotional attachment and family relationship stability. These findings confirm that female PMI migration not only has an impact on economic aspects, but also on the social and psychological well-being of households.